Molecular detection and characterisation of herpesviruses in asymptomatic Russian sturgeon (Acipenser gueldenstaedtii) from European aquaculture - Bergmann Sven Michael; Todte Matthias; Jäger Lea; Lorenzen-Schmidt Fermin Georgio; Jin Yeonwha; Klafack Sandro; Lenk Matthias; Syahidah Dewi; Hastilestari Bernadetta Rina; Penetaseputro Tanjung; Avare Jean-Christophe; Hwang Jeeyoun; et al. (Journal of Veterinary Research)
In Germany, around 150,000 kg of mostly Siberian sturgeon (Acipenser baerii), were produced in 2021. Sudden mortalities affected negative control Russian sturgeon in experimental infection of several European aquacultured fish species with tilapia lake virus (TiLV). An investigation sought the causative agent. In most of the sturgeon, a specific herpesvirus was detected which also occurred in the carp, crucian carp and tench subjects, but not in Nile tilapia. This herpesvirus was latent in the sturgeon population but became productive to cause the outbreak after three weeks of experimentation.